Implementation of Sanctions for Problem Students at Islamic Boarding Schools Darul Hikmah Taman Pendidikan Islam Medan - Rambe, Ardiansah; Hanum, Azizah (Graduate Program Magister Manajemen Pendidikan, 2025)
This study aims to analyze the implementation of sanctions for problematic students at the Darul Hikmah Islamic Boarding School, Taman Pendidikan Islam Medan. As an Islamic educational institution, Islamic boarding schools have an important role in shaping the character and morals of students. However, it is not uncommon to find students involved in violating existing rules. This study uses a qualitative approach with a case study method to explore the understanding of the implementation of sanctions applied in the Islamic boarding school. Data was collected through in-depth interviews with Islamic boarding school administrators, teachers, and students involved, as well as direct observation of the process of implementing sanctions. The results of the study show that the Darul Hikmah Islamic boarding school implements various types of sanctions, ranging from verbal sanctions to physical sanctions that aim to educate and improve student behavior. However, the implementation of these sanctions still faces several challenges, such as differences in perception of the fairness of sanctions and the psychological impact on students. This study suggests the need for periodic evaluation of the sanction system implemented to be more effective in educating students and creating an environment conducive to their spiritual and moral development.